2021
DOI: 10.1017/s0022278x21000057
|View full text |Cite
|
Sign up to set email alerts
|

Media influence on public policy in Kenya

Abstract: Many scholars argue that the media can influence policymakers – determining the policy agenda, framing issues, prioritising issues and, on occasion, setting the policy as well. It could be, however, that skilled policymakers exploit the media, so that the media in fact reflects the issues that policymakers want debated. This then poses an important question of whether the media does indeed influence the public policy process. The topic of media influence is widely studied in consolidated democracies but there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Whilst this may be true of politicians, it is less likely to be true of public officials who, at least in consolidated democracies, are more likely to become specialists in narrow areas of policy. Recent research in Kenya assessed the extent to which the media influenced public officials and concluded that the media secured the attention of policy makers and that there was a modest influence (Irwin & Kiereini, 2021) reflecting conclusions drawn by Walgrave and van Aelst based on studies in developed countries that “media power is extant but modest” (2016: 3). They see two broad types of information requirement: technical information, expert‐based, which explains the problem and may offer possible solutions and political information, which may include an understanding of societal opinion and differences of opinion.…”
Section: Parliamentarians and Sources Of Informationmentioning
confidence: 99%
“…Whilst this may be true of politicians, it is less likely to be true of public officials who, at least in consolidated democracies, are more likely to become specialists in narrow areas of policy. Recent research in Kenya assessed the extent to which the media influenced public officials and concluded that the media secured the attention of policy makers and that there was a modest influence (Irwin & Kiereini, 2021) reflecting conclusions drawn by Walgrave and van Aelst based on studies in developed countries that “media power is extant but modest” (2016: 3). They see two broad types of information requirement: technical information, expert‐based, which explains the problem and may offer possible solutions and political information, which may include an understanding of societal opinion and differences of opinion.…”
Section: Parliamentarians and Sources Of Informationmentioning
confidence: 99%